Is the fox guarding the henhouse? Bankers in the Federal Reserve, bank leverage and risk-shifting - Lim, Ivan; Hagendorff, Jens; Armitage, Seth (Journal of Corporate Finance, 2019)
Nearly 30% of US banks employ at least one board member who currently serves (or has previously served) the Federal Reserve in a public service role. Public service roles take the form of Federal Reserve directorships or memberships in Federal Reserve advisory councils. We show that connections between banks and the Federal Reserve are linked to decreases in the sensitivity of bank leverage to risk. Further, connected banks extract larger public subsidies by shifting risk to the financial safety-net. Jointly, our results suggest that interactions between banks and regulators reduce supervisory effectiveness.